Three-dimensional clustering of Janus cylinders by convex curvature and hydrophobic interactions. Issue 24 (28th June 2015) - Kim, Jongmin; Oh, Myung Seok; Choi, Chang-Hyung; Kang, Sung-Min; Kwak, Moo Jin; You, Jae Bem; Im, Sung Gap; Lee, Chang-Soo
<x xml:space="preserve">Abstract</x> The geometry or degree of hydrophobic interaction in Janus microcylinders affects the formation of the assembled structures.